Characterization of a polysaccharide capsular antigen of septicemic Escherichia coli O115:K "V165" :F165 and evaluation of its role in pathogenicity. - Ngeleka, M (1992)
Escherichia coli strains of serogroup O115:K(-):F165 have been associated with septicemia in calves and piglets. These strains express a capsular antigen referred to as K"V165" which inhibits agglutination of the O antigen by anti-O115 serum. We used hybrid transposon TnphoA mutants M48, 18b, and 2, and a spontaneous O-agglutinable mutant, 5131a, to evaluate the role of K"V165" in the pathogenicity of E. coli O115. Mutant M48 was as resistant to 90% rabbit serum and as virulent in day-old chickens as the parent strain 5131, mutants 18b and 5131a were less resistant to serum and less virulent in chickens, and mutant 2 was serum sensitive and avirulent. Analysis of outer membrane protein and lipopolysaccharide profiles failed to show any difference between the transposon mutants and the parent strain. In contrast, the spontaneous O-agglutinable mutant showed additional bands in the 16-kDa region of the polysaccharide ladder-like pattern. Mutants 2 and 5131a produced significantly less K"V165" capsular antigen than the parent strain, as demonstrated by a competitive enzyme-linked immunosorbent assay with adsorbed anti-K"V165" serum. In addition, electron microscopic analysis revealed that mutants 2 and 5131a had lost the capsular layer observed in the parent strain after fixation with glutaraldehyde-lysine. This capsule contained carbohydrate compounds and resembled an O-antigen capsule since it prevented O-antigen agglutination before the bacteria were heated at 100 degrees C and induced bacterial serum resistance. The capsule-defective mutants colonized the intestinal epithelium of experimentally infected gnotobiotic pigs but failed to induce clinical signs of septicemia. We concluded that E. coli strains of serogroup O115 expressed a polysaccharide capsular antigen which induced serum resistance and consequently contributed to the pathogenicity of the bacteria.